KONSUMSI BAHAN BAKAR MINYAK KOTA SEMARANG DAN KOTA SURAKARTA DITINJAU DARI SISTEM TRANSPORTASI DAN TIPOLOGI KOTA - Mudjiastuti Handajani; Mustakim Aksa (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
Fuel oil is the main fuel in the transportation sector. Transportation system and the city typology influence the fuel consumption of a city. This study aims to analyze and to compare the relationship of transportation system and the typology of the City of Semarang and the city of Surakarta to the fuel consumption of those cities. An analysis was performed using bivariate and multivariate-multivariable regression techniques. Uneven distribution of the population, public transport services dominated by passenger cars, and radial road network result in inefficient fuel consumption in the city of Semarang (0.27 kl/person). Meanwhile an even distribution of the population, public transport services dominated by public bus, and grid road network make fuel consumption more efficient in the city of Surakarta (0.18 kl/person). The use of large-capacity public transport and compact land use can make more efficient use of fuel.